Failure of physiological transformation and spiral artery atherosis: their roles in preeclampsia - Staff, Anne Cathrine; Fjeldstad, Heidi E.; Fosheim, Ingrid Knutsdotter; Moe, Kjartan; Turowski, Gitta; Johnsen, Guro Mørk; Alnaes-Katjavivi, Patji; Sugulle, Meryam (American journal of obstetrics and gynecology, 2022)
Physiological transformation with remodeling of the uteroplacental spiral arteries is key to a successful placentation and normal placental function. It is an intricate process that involves, but is not restricted to, complex interactions between maternal decidual immune cells and invasive trophoblasts in the uterine wall. In normal pregnancy, the smooth muscle cells of the arterial tunica media of uteroplacental spiral arteries are replaced by invading trophoblasts and fibrinoid, and the arterial diameter increases 5- to 10-fold. Poor remodeling of the uteroplacental spiral arteries is linked to early-onset preeclampsia and several other major obstetrical syndromes, including fetal growth restriction, placental abruption, and spontaneous preterm premature rupture of membranes. Extravillous endoglandular and endovenous trophoblast invasions have recently been put forth as potential contributors to these syndromes as well. The well-acknowledged disturbed extravillous invasion of maternal spiral arteries in preeclampsia is summarized, as are briefly novel concepts of disturbed extravillous endoglandular and endovenous trophoblast invasions. Acute atherosis is a foam cell lesion of the uteroplacental spiral arteries associated with poor remodeling. It shares some morphologic features with early stages of atherosclerosis, but several molecular differences between these lesions have also recently been revealed. Acute atherosis is most prevalent at the maternal-fetal interface, at the tip of the spiral arteries. The localization of acute atherosis downstream of poorly remodeled arteries suggests that alterations in blood flow may trigger inflammation and foam cell development. Acute atherosis within the decidua basalis is not, however, confined to unremodeled areas of spiral arteries or to hypertensive disorders of pregnancy and may even be present in some clinically uneventful pregnancies. Given that foam cells of atherosclerotic lesions are known to arise from smooth muscle cells or macrophages activated by multiple types of inflammatory stimulation, we have proposed that multiple forms of decidual vascular inflammation may cause acute atherosis, with or without poor remodeling and/or preeclampsia. Furthermore, we propose that acute atherosis may develop at different gestational ages, depending on the type and degree of the inflammatory insult. This review summarizes the current knowledge of spiral artery remodeling defects and acute atherosis in preeclampsia. Some controversies will be presented, including endovascular and interstitial trophoblast invasion depths, the concept of 2-stage trophoblast invasion, and whether the replacement of maternal spiral artery endothelium by fetal endovascular trophoblasts is permanent. We will discuss the role of acute atherosis in the pathophysiology of preeclampsia and short- and long-term health correlates. Finally, we suggest future opportunities for research on this intriguing uteroplacental interface between the mother and fetus.